Pan-cancer analysis reveals potential of FAM110A as a prognostic and immunological biomarker in human cancer - Zhong, Hongguang; Shi, Qianqian; Wen, Qin; Chen, Jingyi; Li, Xuan; Ruan, Ruiwen; Zeng, Shaocheng; Dai, Xiaofeng; Xiong, Jianping; Li, Li; Lei, Wan; Deng, Jun (Frontiers in Immunology, 2023)
Background: Despite great success, immunotherapy still faces many challenges in practical applications. It was previously found that family with sequence similarity 110 member A (FAM110A) participate in the regulation of the cell cycle and plays an oncogenic role in pancreatic cancer. However, the prognostic value of FAM110A in pan-cancer and its involvement in immune response remain unclear. Methods: The Human Protein Atlas (HPA) database was used to detect the expression of FAM110A in human normal tissues, the Tumor Immune Estimation Resource (TIMER) and TIMER 2.0 databases were used to explore the association of FAM110A expression with immune checkpoint genes and immune infiltration, and the Gene Set Cancer Analysis (GSCA) database was used to explore the correlation between FAM110A expression and copy number variations (CNV) and methylation. The LinkedOmics database was used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Statistical analysis and visualization of data from the The Cancer Genome Atlas (TCGA) or the Genotype–Tissue Expression (GTEx) databases were performed using the R software (version 3.6.3). Clinical samples were validated using immunohistochemistry. Results: FAM110A expression was elevated in most tumor tissues compared with that in normal tissues. CNV and methylation were associated with abnormal FAM110A mRNA expression in tumor tissues. FAM110A affected prognosis and was associated with the expression of multiple immune checkpoint genes and abundance of tumor-infiltrating immune cells across multiple types of cancer, especially in liver hepatocellular carcinoma (LIHC). FAM110A-related genes were involved in multiple immune-related processes in LIHC. Conclusion: FAM110A mRNA is abnormally expressed in various cancer types and participates in regulating the immune response of the body, thus affecting the prognosis of patients. FAM110A may serve as a prognostic and immunological biomarker for human cancers.